Numerical simulation of seepage maps under dams with sheet piles on their ends. Issue 1 (17th February 2019) - Martínez‐Moreno, Encarnación; Alhama Manteca, Iván; García‐Ros, Gonzalo
Abstract : Seepage maps formed by both stream and equipotential lines, emerging under dams with sheet piles on their ends, can be determined by simulating the Laplace conjugate equations using a numerical technique such as the network method. Based on these maps, engineers can immediately deduce the amount of water circulating under the structure and design the sheet piles depth to safe values that allow to limit risks such as siphoning or erosion of the base of the dam. For a fix depth of the upstream sheet pile, seepage maps are shown for different configurations of the downstream sheet pile, in a 2D scenario with finite depth and with large extensions both upstream and downstream of the dam.